MEANING RELATION OF HYPONYM IN BATAK TOBA LANGUAGE - Rezeki, Tri Indah; Mulyadi, Mulyadi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
In semantic relations, hyponymy is a relationship where a more specialized word (the hyponym) can be categorized under a more general or generic term (the hypernym). Understanding hyponymy helps elucidate how words and phrases relate to each other in terms of meaning, allowing for the classification of concepts and objects based on their specificity or generality. This research aimed to describe the hyponymic meaning relations found in Batak Toba songs and to explain the types of hyponyms used, particularly in these songs. The study employed a descriptive qualitative research method. The data comprised Batak Toba song lyrics sourced from a YouTube video uploaded on April 23, 2021 (https://www.youtube.com/watch?v=dtSRkD9WyPU), containing fourteen songs that featured hyponymic relations. Data collection involved listening and note-taking techniques, while data analysis was guided by the theory of hyponymy proposed by Croft and Cruse. The analysis identified ten hyponymic words within the song lyrics. The study concluded that Batak Toba songs utilize hyponymic meaning relations, demonstrating how specific terms are subsumed under more general categories.